1994
DOI: 10.2337/diacare.17.12.1473
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of IDDM in Seoul From 1985 to 1988

Abstract: The incidence rate of IDDM in Seoul is the lowest reported in the world. This might be effectively considered a baseline incidence rate before exposure to environment or other risk factors. The similar pattern of onset characteristics in Korea to those in other countries suggests that the same etiological factors are operative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 6 publications
3
31
2
1
Order By: Relevance
“…First, for the case-control association study, 119 type 1 diabetic patients were selected randomly from the Korean Seoul Registry (5,6,15). All patients MICA and type 1 diabetes were on insulin therapy upon hospital discharge, Ͻ15 years of age, and residents of Seoul at the time of disease onset.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, for the case-control association study, 119 type 1 diabetic patients were selected randomly from the Korean Seoul Registry (5,6,15). All patients MICA and type 1 diabetes were on insulin therapy upon hospital discharge, Ͻ15 years of age, and residents of Seoul at the time of disease onset.…”
Section: Subjectsmentioning
confidence: 99%
“…All patients MICA and type 1 diabetes were on insulin therapy upon hospital discharge, Ͻ15 years of age, and residents of Seoul at the time of disease onset. Their mean age was 13 years (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The second group consisted of 134 nondiabetic control subjects with no family history of diabetes who were selected from the same geographical area.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was also reported that only 1.7 % (2 of 121) of previously undetected Type II diabetic patients in Korea had anti-GAD antibody [28]. Taken together with the finding that the incidence of Type I (insulin-dependent) diabetes in Japan and Korea is among the lowest in the world [29,30], these results suggest that autoimmunity might not be a major cause of diabetes in this country.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, it is difficult to perform studies regarding type 1 diabetes mellitus in Asia, including Korea and Japan, due to the low incidence of type 1 diabetes mellitus [17,18]. Therefore, it is uncertain how many patients with type 1 diabetes in Korea ing the greatest r value for the correlation with other indexes was considered to be the best parameter.…”
Section: Measurements and Data Analysismentioning
confidence: 99%